ANALISIS KESESUAIN (HOTS) HIGHER ORDER THINKING SKILL PADA ASESMEN SASTRA DI BUKU ERLANGGA DAN BUKU SEKOLAH ELEKTRONIK (BSE) KELAS XI SMA - Nanang Bustanul Fauzi; Jamila Wijayanti; Makhrus Abadi (JURNAL ILMIAH EDUNOMIKA, 2021)
To meet the need for cheap textbooks, the government took the initiative to compile School Electronic Books (hereinafter abbreviated as BSE). However, their popularity is still far behind other commercial books, for example the book published by Erlangga. This fact raises questions regarding the quality of BSE. If so, there is an indication that the quality of BSE is lower than the books published by Erlangga so that it is more of an option than the free BSE. This indication can be formulated by questions (1) Is the quality of BSE lower than Erlangga? (2) how is the suitability of HOTS questions?, (3) is BSE less suitable with HOTS compared to Erlangga ?, and (4) based on the two previous studies it can be concluded that the questions using HOTS have good quality in evaluating students. Meanwhile, in fact, there are still textbooks that have not fully used HOTS (Maharani [2015] and Julianingsih [2017]). This research uses a qualitative approach. The data obtained is in the form of qualitative data sourced from teaching materials for school electronic books (BSE) in the subject of Indonesian language class X SMA revision edition 2017. The data in this study are assessments used or generated by teaching materials in electronic school books (BSE). From the assessment, the types of assessment are analyzed, the operational verbs used, and the suitability of the operational verbs used with HOTS. Keywords: textbooks, BSE book, HOTS compatibility